Plan quinquinal de marketing para la empresa procesadora de agua israel en el cantón Lago Agrio - Dávalos Lema, Alexandra Lorena (2016)
The processing company of Agua Israel, is an entity dedicated to the production and marketing of bottled water, which must face a high level of competitiveness due to the presence of companies that operate outside the law, as they do not meet the requirements Legal or health that requires the commercialization of this product. Likewise, it was determined that the company does not plan strategies based on the 4 Ps, limiting its capacity to respond to changes in the environment. In view of the described situation, it was considered important to develop the five-year marketing plan, which allows to face the changes of the environment through previously analyzed proposals that contribute to improve the positioning of the company in the market. Through the approach of the literature review, it was theoretically determined the process to be followed for the elaboration of the quinquennial marketing plan, afterwards it is exposed the methodology used that include the methods, establishment of the population under study and the techniques for the collection of information . A situational diagnosis was then carried out, in which the analysis of the external environment of the company was carried out, determining a weighted total of 2.35 which means that the business is in an unfavorable position since there are threats that may affect its operations; While in the analysis of the internal environment it reached a weighted rating of 2.50, that is, it is in the established standard which indicates that its strengths are balanced with its weaknesses, however, actions can be taken to eliminate weaknesses and highlight strengths. The study carried out five strategic objectives: "To promote a campaign of care of the environment, that allows the sustainable growth of the company", "to extend the range of products, in order to satisfy the market demand" to define a plan Promotional, which offers preferential prices to loyal customers to the company "," implement payment plans, allowing the| customer facilities that fit their needs "and" establish an advertising campaign that allows to efficiently disseminate the image of the company " . The proposed proposal requires an investment of $ 8.003,34 investment that seeks to position the product, which will bring greater revenue to the company, allowing it to maintain its economic stability and face strong competition, benefiting both employees and society in general thanks To the wealth generated by business stability.